AUGMENTED REALITY IN FOREIGN LANGUAGE LEARNING: ENCHANCING VOCABULARY ACQUISTION THROUGH IMMERSIVE EXPERIENCES - Ardi Azhar Nampira; Rit Som; Som Chai; Utary Rustam (Lingeduca: Journal of Language and Education Studies, 2025)
Foreign language learning continues to face persistent challenges, particularly in vocabulary acquisition, which is often constrained by decontextualized instruction and limited learner engagement. Recent advances in educational technology suggest that augmented reality (AR) can offer immersive and interactive learning environments capable of addressing these limitations. This study aims to examine the effectiveness of augmented reality–based instruction in enhancing vocabulary acquisition among foreign language learners through immersive learning experiences. The research employed a quasi-experimental design involving an experimental group receiving AR-supported vocabulary instruction and a control group taught using conventional methods. Data were collected through pre-tests and post-tests, classroom observations, and learner perception questionnaires, and were analyzed using both descriptive and inferential statistical techniques. The findings indicate that learners exposed to augmented reality demonstrated significantly higher vocabulary gains, improved retention, and greater learning motivation compared to those in the control group. Qualitative data further revealed that immersive visual and contextual cues facilitated deeper semantic understanding and learner engagement. The study concludes that augmented reality is a pedagogically effective tool for foreign language vocabulary instruction, offering meaningful, context-rich learning experiences. These results suggest that integrating AR into foreign language curricula can substantially enhance vocabulary learning outcomes and learner motivation, while also supporting innovative, technology-enhanced pedagogical practices.